PENGARUH SOSIAL PROOF DAN PUBLIC RELATION TERHADAP CUSTOMER RETENTION - Anisa Aliya (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study analyzes the influence of social proof and public relations on customer retention in Mobile Heloo Coffee MSMEs in Bengkulu City. This study uses a quantitative approach and the research population is all active customers of Mobile Heloo Coffee MSMEs in Bengkulu City, with a sample of 110 respondents who were selected purposively. Primary data was collected through a Likert scale-based questionnaire instrument which was distributed directly to respondents. Data analysis was carried out using the SPSS version 26 device with multiple linear regression method. The results showed that social proof and public relations had a positive and significant effect on customer retention, explaining 76,0% of the variation (the remaining 24,0% by other factors). The implications of the study show that Kopi Heloo Keliling MSMEs need to optimize social proof strategies through attractive social media content and strengthen public relations with excellent service through mobile cart mobility to increase customer loyalty in a sustainable manner. Keywords: Social proof, Public relations, Customer Retentio